2007
DOI: 10.1080/01916122.2007.9989641
|View full text |Cite
|
Sign up to set email alerts
|

The palynology of the Cerrejón formation (Upper Paleocene) of northern Colombia

Abstract: A palynological study of the Cerrejon Formation was conducted in order to date the formation and understand the floristic composition and diversity of a Paleocene tropical site. The Cerrejon Formation outcrops in the Cerrejon Coal Mine, the largest open cast coal mine in the world. Two cores (725 m) were provided by Carbones del Cerrejon LLC for study. Two hundred samples were prepared for palynology, and at least 150 palynomorphs were counted per sample where possible. Several statistical techniques including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
3
28
0
2
Order By: Relevance
“…Various authors (Dueñas, 1980;Monsh, 1998;Jaramillo and Dilcher, 2000;Pardo-Trujillo et al, 2003;Helenes and Cabrera, 2003;Silva, 2004;Jaramillo et al, 2007;Latrubesse et al, 2007) have indicated that the climate in the Amazonia region and north of South America, was, in general, hot and wet during the Middle/Late Miocene. This interpretation is justified by the marked presence of Gramineae, Palmae, and aquatic algae, as well as the presence of crocodilians, which are unequivocal indicators of floodplain environments (Riff et al, 2010).…”
Section: Composition Of the Palynoflora And Paleoenvironmental Interpmentioning
confidence: 98%
“…Various authors (Dueñas, 1980;Monsh, 1998;Jaramillo and Dilcher, 2000;Pardo-Trujillo et al, 2003;Helenes and Cabrera, 2003;Silva, 2004;Jaramillo et al, 2007;Latrubesse et al, 2007) have indicated that the climate in the Amazonia region and north of South America, was, in general, hot and wet during the Middle/Late Miocene. This interpretation is justified by the marked presence of Gramineae, Palmae, and aquatic algae, as well as the presence of crocodilians, which are unequivocal indicators of floodplain environments (Riff et al, 2010).…”
Section: Composition Of the Palynoflora And Paleoenvironmental Interpmentioning
confidence: 98%
“…racematus in the studied material) are known from the Oligocene of Cameroon (Salard-Cheboldaeff, 1979) and the Maastrichtian to Oligocene of Sudan (Awad, 1994;Stead and Awad, 2005). South American records are from the Maastrichtian to Eocene ( Van der Hammen, 1954;González Guzmán, 1967;Ravn, 1998;Jaramillo et al, 2007). In addition González Guzmán (1967) and the Taxon database (Ravn, 1998) also mention an undifferentiated Upper Cretaceous occurrence (not included in Fig.…”
Section: Palynostratigraphic Resultsmentioning
confidence: 95%
“…Previous records of Retidiporites magdalenensis are from the Maastrichtian of Nigeria, Egypt, Somalia (Lawal and Moullade, 1986;Schrank, 1987Schrank, , 1994a, the Maastrichtian to Paleocene of Nigeria (Germeraad et al, 1968; and Sudan (Awad, 1994) and the interval Maastrichtian to Eocene of the Caribbean (Germeraad et al, 1968), Colombia (Jaramillo et al, 2007) and several West African basins (Salard-Cheboldaeff, 1990). Retidiporites magdalenensis (together with Monocolpites marginatus) is regarded by Lawal and Moullade (1986, p. 72) as a Maastrichtian marker.…”
Section: Palynostratigraphic Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…About 35% of its population is illiterate and 65.2% fail to have their basic needs met (Departamento Nacional de Planeación -DNP, 2014). Contributing to about 60% of La Guajira's gross domestic product (Balch 2013), Cerrejón is the largest producer of coal in Colombia, and the biggest open pit coal operation in the world (Jaramillo et al 2007). It is a joint venture owned by BHP Billiton, Anglo American and Xstrata Coal, in operation since 1976.…”
Section: Human Development Index and Resource Districts Of Colombiamentioning
confidence: 98%